“So this is my new life”: A Qualitative Examination of Women Living with Multiple Sclerosis and the Coping Strategies They Use When Accessing Physical Activity - Margaret Schneider; Nadine Young (Disability Studies Quarterly, 2010)
The purpose of this study was to explore the lived experiences of women living with multiple sclerosis and their perceived barriers to accessing physical activity. Seven women were invited to complete a background questionnaire and a semi-structured interview to discuss these experiences, and to examine any perceived barriers (i.e., internal and external) that they encountered in relation to physical activity. The key themes that emerged from the interpretive analysis were the apparent importance of: 1) self-management; 2) treatments; and 3) attitude, when accessing such opportunities. The findings suggest that it is important for physicians to understand the patient’s experience of living with multiple sclerosis and the impact of the disease can have on other aspects of their life (e.g., access to physical activity). Acknowledgement of this experience and the issues that these women struggle with on a daily basis could enhance the physician/patient relationship, and encourage a more collaborative effort in terms of establishing an illness management plan for navigating the illness journey.